(untitled) (The International Research Journal of Management Science, 2024)
Purpose: The main purpose of this paper is to delineate the concept and challenges of sustainable human resource management (sustainable HRM) to manage people from an outside-in approach. Methodology/Design: This paper is a very conceptual type and presents the views of authors drawn from the scholarly contributions of human-side enterprises in the context of business as usual, corporate social responsibility, triple bottom line, and sustainable development goals (SDGs-2030). Findings: Since concepts and perspectives of sustainable HRM are emerging, there are challenges to designing and implementing it from an outside-in approach. Traditional organizational structure, inadequate reward, role conflict, ambiguity, and support from management and shareholders are some of the challenges. However, since sustainable HRM is an ethical responsibility to the survival and longevity of businesses/organizations through promoting environmental, economic, and social advantages in the long run, stakeholders could be interested and benefit from it. Research limitations/Implications: Adequate scientific inquiry is required in the future to comprehend sustainable HRM concepts, practices, challenges, and outcomes in relation to SDGs to promote the common good. Practice implications: Since Nepal has ratified the SDGs and incorporated these goals into the national development plan, it is the responsibility of private, public, and higher education institutions to act in accelerating the SDG movement to cope with economic, environmental, and social challenges at the organizational level through transforming HRM purposes. Originality/value: This study highlights the need for a paradigm shift in management practices by framing HRM transformation within the "Common Good Agenda" and positioning HRM as a force for positive social change through an outside-in approach. Such an approach would be especially relevant in light of corporate social responsibility (CSR) programs and sustainable development goals (SDGs).